2019
DOI: 10.3390/biom9050197
|View full text |Cite
|
Sign up to set email alerts
|

Clove Essential Oil as an Alternative Approach to Control Postharvest Blue Mold Caused by Penicillium italicum in Citrus Fruit

Abstract: Penicillium italicum causes blue mold disease and leads to huge economic losses in citrus production. As a natural antifungal agent, clove essential oil (CEO), which is a generally recognized as safe (GRAS) substance, shows strong in vitro activity against fungal pathogens. However, few studies on CEO for controlling postharvest blue mold disease caused by P. italicum in citrus fruit have been reported. Our aims were to investigate the control efficacy and possible mechanisms involved of CEO against P. italicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
68
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 45 publications
11
68
0
1
Order By: Relevance
“…The current knowledge suggested that the ZOI of P. digitatum increased in a dose-dependent manner, indicating significant inhibition of the growth of P. digitatum by the X33 antifungal extract. In addition to the antifungal agents thymol ( Perezalfonso et al, 2012 ), chitosan oligomers ( Lu et al, 2014 ), clove essential oil ( Chen et al, 2019a ), and trans-cinnamaldehyde ( Huang et al, 2019 ), this study suggests a novel fungicide to control citrus postharvest green mold. Compared to other antifungal agents, the X33 antifungal extract, a poly-L-lysine analog derived from S. lavendulae , exhibited excellent antifungal activity.…”
Section: Discussionmentioning
confidence: 99%
“…The current knowledge suggested that the ZOI of P. digitatum increased in a dose-dependent manner, indicating significant inhibition of the growth of P. digitatum by the X33 antifungal extract. In addition to the antifungal agents thymol ( Perezalfonso et al, 2012 ), chitosan oligomers ( Lu et al, 2014 ), clove essential oil ( Chen et al, 2019a ), and trans-cinnamaldehyde ( Huang et al, 2019 ), this study suggests a novel fungicide to control citrus postharvest green mold. Compared to other antifungal agents, the X33 antifungal extract, a poly-L-lysine analog derived from S. lavendulae , exhibited excellent antifungal activity.…”
Section: Discussionmentioning
confidence: 99%
“…Medicinal plant extracts and their bioactivators are being paid increasing attention by researchers due to their potential to control fungal growth as well as their preservative effects [3,21,25,30,37,38]. Among plant extracts, Ficus hirta Vahl.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of P7G on lesion diameter and disease severity in navel oranges were determined following the method previously described with slight modifications [30,31]. The sterilized navel oranges were wounded (4 mm diameter and 2-mm deep) using a sterile puncher at the equatorial side on each fruit, and then divided in five randomized groups for various P7G treatment levels (0, 1, 2, 4, and 8 g/L).…”
Section: In Vivo Antifungal Activity Assay On Navel Orange Fruitmentioning
confidence: 99%
See 2 more Smart Citations